Effect of prolonged starvation on nutrition utilization and transcriptional responses in Pacific oyster (Crassostrea gigas) - Mingkun Liu; Chenchen Wei; Wenwen Xu; Lintao Tan; Li Li; Guofan Zhang (Aquaculture Reports)
Emaciation syndrome due to starvation is a significant cause of mortality in marine animals, yet the underlying mechanisms in non-feeding and weak/no-mobility marine bivalves remain poorly understood. This study investigated nutrient utilization and transcriptional responses in oysters subjected to a 44-day starvation period. Nutrient analysis revealed a distinct three-phase pattern in nutrient utilization. During the early stage (days 0–10), glycogen was rapidly consumed, with no mobilization of lipids, proteins, or fatty acids. In the late stage (days 23–44), glycogen was depleted, and there was significant consumption of lipids, proteins, fatty acids, and free amino acids. A newly identified ''transition metabolism'' phase, occurring between the two typical phases (days 10–23), was characterized by a slight compensatory increase in glycogen and lipids, alongside continued protein consumption and depletion of five fatty acids. This phase may represent ''the point of no return'' in starvation tolerance. Transcriptomic analysis revealed that the amino acid and lipid metabolism increased over starvation, while carbohydrate metabolism initially rose and then declined, with a notable tipping point on day 10. This pattern strongly supported the stepped change pattern identified by nutrient utilization. In contrast, immunological functions initially decreased before increasing, whereas functions related to cell growth and survival showed a consistent downward trend. Combined with the correlation between gene expression and symbiotic microbiota, these findings indicated that oysters, due to limited energy, activated insufficient immune responses, leading to increased pathogen abundance and higher mortality during prolonged starvation. This study refined the starvation stress tolerance limits (SSTL) model to better characterize oyster performance under prolonged starvation, offering valuable insights into emaciation syndrome and potential indicators for assessing health status and mortality risk in marine bivalves.